CD8+ T cells stimulate Na-Cl co-transporter NCC in distal convoluted tubules leading to salt-sensitive hypertension - Yunmeng Liu (Nature Portfolio, 2017)
T cells contribute to development of high blood pressure but their role in salt-sensitive hypertension is less clear. Liuet al. show that CD8+ T cells upregulate and activate Na-Cl co-transporter NCC in distal convoluted tubules via direct cell-cell contact and ROS-Src activation, leading to Na+retention and salt-sensitive hypertension.